PENERAPAN RETORATIVE JUSTICE DALAM TINDAK PIDANA KECELAKAAN LALU LINTAS YANG DILAKUKAN OLEH ANAK DI SATLANTAS POLRES NIAS SELATAN - Anugrah Sellamat Laia (Jurnal Panah Hukum, 2026)
A traffic accident is an event that occurs on a highway that is unexpected and intentional involving vehicles and road users, which causes human casualties and damages property. Traffic accidents are caused by violations and negligence of drivers involving members of the public regardless of age. Traffic accidents involving minors can occur due to several factors, including parents allowing their children to use vehicles, especially motorbikes, using vehicles at high speed, lack of legal awareness, and which can sacrifice the lives and property of both the driver and other people. One of the traffic accident crimes that has been resolved using restorative justice at the South Nias Police Traffic Unit, namely, a traffic accident committed by a child on December 10 2023. This crime has been resolved and the sanctions given to the child include an apology and compensation for damage to the victim's vehicle, but in the settlement the child was not present. The type of research used is sociological legal research, by going into the field to analyze what actually happens in society. The data collection techniques used were primary and secondary legal materials, primary legal data was obtained from interviews. Data analysis used in this research was descriptive qualitative analysis and conclusions were drawn using a deductive method. Based on the research findings and discussion, it can be concluded that the implementation of Restorative Justice has been implemented and is not in accordance with Police Regulation Number 8 of 2021. Because the perpetrator was not present in peace between the perpetrator and the victim. The author suggests that the South Nias Police Traffic Unit, in implementing Restorative Justice, should bring together the parties, especially the perpetrator and the victim, so that the resolution is in accordance with the applicable laws and regulations.